PRAGMATIC ANALYSIS OF POLITENESS STRATEGY IN SOCIAL MEDIA COMMUNICATION IN BIGMO YOUTUBE VIDEOS - Citra Nurjanah; Friska Ruth Margareth Purba; Sonya Trikandi; Fidiatun adiyan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Social media communication serves not only as a means of conveying information but also as a medium that reflects the use of politeness strategies in maintaining interpersonal relationships. One example of such communication can be found in Bigmo's YouTube podcast, which features spontaneous and interactive conversations. This study aims to analyze the politeness strategies used in social media communication in Bigmo's YouTube video entitled "All Streaming Belongs to Allah...(BIGMO x ALDI TAHER!!!)" based on Brown and Levinson's (1987) politeness theory. This study employed a descriptive qualitative method with a pragmatic approach. The data consisted of utterances containing politeness strategies found in the selected YouTube video. The data were analyzed through three stages: data reduction, data display, and conclusion drawing. The findings revealed that all four politeness strategies proposed by Brown and Levinson were identified, namely bald on-record (16 utterances), positive politeness (31 utterances), negative politeness (4 utterances), and off-record (6 utterances). Among these strategies, positive politeness was the most frequently used, while off-record was the least frequently employed. These findings indicate that the speakers tended to prioritize strategies that promote closeness, solidarity, and friendly interpersonal relationships in social media communication.